Implementasi Keteladanan Guru Dalam Pembentukan Karakter Siswa Kelas 3 SD Muhammadiyah 21 Baluwarti Tahun Ajaran 2016/2017 - Iswari, Nurlita, Dra. Sri Hartini, S.H, M.Pd (2017)
This study aims to describe the 1) the teacher's example forms in the formation of character grade III 2) implementation of teacher's example in the formation of character grade III. This type of research is qualitative. Using the method of data collection techniques interviews, observation and documentation. Data analysis techniques using interactive analysis. The validity of the data using triangulation techniques and sources. The conclusion that can be drawn is 1) form example of teachers in the formation of character grade III i.e. a) example of doing honest include teaches said for what it is, recognize errors, teach the practise questions honestly b) example of discipline include wear uniforms appropriate provisions, came to school early c) noble moral example include activities memorizing the short letter, read Wrote the Quran 30ru, and the Congregation d) example shows his intelligence include teaches modesty, afford colonised the material, creating a fun learning e) example acted independently and work hard that is always engaging students in learning, enterprising and eager while teaching. 2) Implementation example teacher already applied with the best possible teachers performed starting from the teacher himself by becoming an example for their students, teachers give moral and motivation in students. Implementation example teacher is done through three stages, namely a) perencanakan with a teacher and school principal b) implementation by applying time activities at school c) assessment by way of a direct look at the development of the students. Example done repeatedly so that children are interested in emulating and getting used to with positive things and done in cooperation between the school and the parents.